PENGGUNAAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PROSES PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Afrinariza, Afrinariza; Taufina, Taufina; Amini, Risda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the use of the Discovery Learning model to improve the integrated thematic learning process in the fifth grade of SD Kartika I-11 Padang. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection. The subjects of this study were researchers, teachers, and fifth grade students of SD Kartika I-11 Padang, totaling 20 people. The results of the study were: (1) the percentage of lesson plan observation was 76.6%, an increase of 93.75%. (2) Teacher activities 79.7%, an increase of 90.6%. (3) Student activities 79.7%, an increase of 90.6%. Keywords: Integrated thematic learning, Discovery Learning